Kisah Nabi Ayyub Dalam QS. Al-Anbiya’ Ayat 83-84: “Analilis Hermeneutika Wilhelm Dilthey” - Dita, Dita Erlin Enjelina; Anam, Wahidul (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
The story of prophet Ayyub is a piece of the story of the prophets who were tested by God with a very powerful test, namely with an illness that did not heal, lost his children and property, lived away from society. With Wilhelm Dilthey's hermeneutic approach, there are three stages in analyzing, namely, Erlebnis (inner experience), Ausdruck (expression) and Verstehen (understanding). In applying Wilhelm Dilthey's three stages of analysis to the study of Q.S Al-Anbiya' verses 83-84, namely, wanting to know the deep meaning and lessons contained in the verse. In this study the author found that the erlebnis is the experience of Prophet Ayyub with the pain and trials that forged his life. The Ausdruck is that the prayer of prophet Ayyub is an expression of faith and hope for help from God. then Verstehen (understanding) that we can take from the story of prophet Ayyub is that a test is part of human life that must be faced with patience and faith in God. then we must believe that God always hears the prayers of His earnest servants. this illustrates the compassion and power of the Great God. The wisdom that can be taken from the story of Prophet Ayyub and we apply it today is like being patient when facing trials, always being istiqamah in worship, trusting in Allah, and always being grateful in everything.